Child Injury Prevention - David C. Schwebel (Ed.) (MDPI - Multidisciplinary Digital Publishing Institute, 2014)
Injuries are among the leading causes of child morbidity and mortality worldwide [1]. Because injuries typically are incurred by healthy children engaging in daily activities, they can be particularly devastating to the injured child and his or her family, disrupting otherwise mentally and physically healthy lives with tragic short- and long-term consequences. Despite the implication of the lay term "accident", injuries are preventable. The global community of scholars and practitioners is slowly creating, discovering, and implementing programs to reduce the burden of injury on the world's youth. This volume contributes to those objectives. [1...]